Comparing Self-Reported Sugar Intake With the Sucrose and Fructose Biomarker From Overnight Urine Samples in Relation to Cardiometabolic Risk Factors - Ramne, Stina; Gray, Nicola; Hellstrand, Sophie; Brunkwall, Louise; Enhörning, Sofia; Nilsson, Peter M.; Engström, Gunnar; Orho-Melander, Marju; Ericson, Ulrika; Kuhnle, Gunter G. C.; Sonestedt, Emily (Frontiers in Nutrition, 2020)
Studies on sugar intake and its link to cardiometabolic risk show inconsistent results, partly due to dietary misreporting. Cost-effective and easily measured nutritional biomarkers that can complement dietary data are warranted. Measurement of 24-hour urinary sugars is a biomarker of sugar intake, but there are knowledge gaps regarding the use of overnight urine samples. We aim to compare 1) overnight urinary sucrose and fructose measured with liquid chromatography-tandem mass spectrometry, 2) self-reported sugar intake measured with web-based 4-day food records, 3) their composite measure, and 4) these different measures’ (1-3) cross-sectional associations with cardiometabolic risk factors in 991 adults in the Malmö Offspring Study (18-69 years, 54% women). The correlations between the reported intakes of total sugar, added sugar and sucrose was higher for urinary sucrose than fructose, and the correlations for the sum or urinary sucrose and fructose (U-sugars) varied between r≈0.2-0.3 (P<0.01) in men and women. Differences in the direction of associations were observed for some cardiometabolic risk factors between U-sugars and reported added sugar intake, as well as between the sexes. In women, U-sugars, but not reported added sugar intake, were positively associated with systolic and diastolic blood pressure and fasting glucose. Both U-sugars and added sugar were positively associated with BMI and waist circumference in women, whereas among men, U-sugars were negatively associated with BMI and waist circumference, and no association was observed for added sugar. The composite measure of added sugars and U-sugars was positively associated with BMI, waist circumference and systolic blood pressure and negatively associated with HDL cholesterol in women (P<0.05). Conclusively, we demonstrate statistically significant, but not very high, correlations between reported sugar intakes and U-sugars. Results indicate that overnight urinary sugars may be used as a complement to self-reported dietary data when investigating associations between sugar exposure and cardiometabolic risk. However, future studies are highly needed to validate the overnight urinary sugars as a biomarker because its use, instead of 24-hour urine, facilitates data collection.